Seasons of her life : a biography of Madeleine Korbel Albright - Blackman, Ann (New York, NY Scribner, 1998)
The first comprehensive biography of Madeleine Albright. An objective yet deeply personal portrait of the only female Secretary of State & the highest-ranking woman in the American government. Provided by the publisher.
D., 9/01
Keywords: Albright, Madeleine Korbel; Women cabinet officers--United States--Biography; Cabinet officers--United States -- Biography; United Nations--Officials and employees -- Biography; Ambassadors--United States -- Biography